2010
DOI: 10.1590/s0100-69912010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Hérnia intercostal transdiafragmática após fratura espontânea de costelas secundária à crise de tosse

Abstract: One case of transdiafragmatic intercostal hernia after intense coughing fit followed by rib fractures in patient with history of pneumonia is presented. He had a severe coughing fit, developed a right toracoabdominal hematoma and then a tumor that was gradually enlarging. Image exams confirmed the diagnosis. Treatment consisted of surgical repair with the use of a polypropylene prosthetic mesh. It is a rare type of hernia. Only four cases were found in literature. The sooner the disease is diagnosed and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Spontaneous fractures of the ribs due to cough are rare but cough-induced hemothorax have rarely been reported. 35 Most cases occur due to severe coughing. These fractures are thought to occur due to one of the two mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous fractures of the ribs due to cough are rare but cough-induced hemothorax have rarely been reported. 35 Most cases occur due to severe coughing. These fractures are thought to occur due to one of the two mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, only one case of SHP was reported in Colombia in 2015, which was solved by video-assisted thoracic surgery (VATS) using a polypropylene mesh (14). Other publications have only reported intercostal or transdiaphragmatic hernias involving abdominal cavity structures (15,16), which are normally the result of thoracoabdominal trauma (17) 2), identified pulmonary herniations in tuberculous or chronic bronchitis patients and reported that they were caused by the patients' effort due to repeated coughing. Kronenberger (23), on the other hand, addressed some costal fractures that he referred to as spontaneous, but he did not specify their etiology.…”
Section: Discussionmentioning
confidence: 99%
“…En América Latina no hay reportes publicados de hernias pulmonares y tan sólo se han reportado algunos casos de hernias intercostales transdiafragmáticas con contenido de estructuras de la cavidad abdominal 34,35 , todos corregidos con cirugía abierta, mediante toracotomía, y reparo del defecto herniario con material protésico. Tampoco hay reportes de cirugía mínimamente invasiva.…”
Section: Discussionunclassified